P371 Using digital monitoring during the COVID pandemic to streamline outpatient appointments. (27th May 2021) - Walsh, A J; Matini, L; Wilson, J; Lyden, S; Al-Hillawi, L; Kantschuster, R; Kormilitzin, A; Smith, T; Slater, J; Payton, S; White, L; Woodley, H; et al.
Abstract: Background: Demand for outpatient appointments (OPAs) for IBD often exceeds capacity, partly due to scheduled follow up of patients who are well. The TrueColours-IBD (TC-IBD) platform and Escalation of Therapy or Intervention (ETI) calculator was trialed as a tool to triage appointments during the pandemic Methods: TC-IBD is a web-based programme of email prompts linked to validated disease-specific indices. The ETI calculator was created after logistic regression showed that patient-reported symptoms and quality of life could calculate the probability of therapy escalation or intervention during an OPA (Fig 1). A score ≤20 equates to ≤10% chance of escalation The ETI calculator was developed for UC, but it was also applied to CD during the pandemic, replacing the SCCAI score with HBI. From Mar-Oct 2020 the ETI calculator was used to extend 145 OPAs (87 UC, 58 CD) from 1034 ETI assessments. TC-IBD data was assessed 2-6 weeks before a scheduled OPA. Patients were eligible for OPA extension if >2 symptom (SCCAI/HBI) and 1 QoL responses (IBD Control) within 4 weeks and ETI score ≤20. Patients with extended OPAs were monitored for 3 & 6-monthly ICHOM outcomes (www.ichom.org ), collected through the TC-IBD platform Results: ICHOM outcomes available for 113/145 patients at 3 mo and 125/145 patients at 6 mo. There were no emergency department visits, no hospitalisations, no surgery, colon cancer or death at either time point in patients whose appointment was extended. 1 patient with UC required prednisolone (Table 1) Conclusion: Routine digital monitoring of symptoms, quality of life and PROMs can safely streamline outpatient care in IBD